Formation of chlorate and perchlorate during electrochemical oxidation by Magnéli phase Ti4O7 anode: inhibitory effects of coexisting constituents - Lu Wang; Yaye Wang; Yufei Sui; Junhe Lu; Baowei Hu; Qingguo Huang (Scientific Reports, 2022)
Abstract Formation of chlorate (ClO3 −) and perchlorate (ClO4 −) as by-products in electrooxidation process has raised concern. In the present study, the formation of ClO3 − and ClO4 − in the presence of 1.0 mM Cl− on boron doped diamond (BDD) and Magneli phase titanium suboxide (Ti4O7) anodes were evaluated. The Cl− was transformed to ClO3 − (temporal maximum 276.2 μM) in the first 0.5 h on BDD anodes with a constant current density of 10 mA cm2, while approximately 1000 μM ClO4 − was formed after 4.0 h. The formation of ClO3 − on the Ti4O7 anode was slower, reaching a temporary maximum of approximately 350.6 μM in 4.0 h, and the formation of ClO4 − was also slower on the Ti4O7 anode, taking 8.0 h to reach 780.0 μM. Compared with the BDD anode, the rate of ClO3 − and ClO4 − formation on the Ti4O7 anode were always slower, regardless of the supporting electrolytes used in the experiments, including Na2SO4, NaNO3, Na2B4O7, and Na2HPO4. It is interesting that the formation of ClO4 − during electrooxidation was largely mitigated or even eliminated, when methanol, KI, and H2O2 were included in the reaction solutions. The mechanism of the inhibition on Cl− transformation by electrooxidation was explored.